Commingled and Disarticulated Human Remains Working Toward Improved Theory, Method, and Data - Osterholtz, Anna J.; Baustian, Kathryn M.; Martin, Debra L.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Commingled and Disarticulated Human Remains: Working Toward Improved Theory, Method, and Data brings together research that provides innovative methodologies for the analysis of commingled human remains. It has temporal and spatial breadth, with case studies coming from pre-state to historic periods, as well as from both the New and Old World. Highlights of this volume include standardized methods and the presentation of best practices in the field. Using a case study approach, the volume demonstrates how data gathered from commingled human remains can be incorporated into the overall interpretation of a site and explores the best ways to formulate the demographic makeup of commingled assemblages. Field archaeologists, bioarchaeologists, academic anthropologists, forensic anthropologists, zooarchaeologists, and students of anthropology and archaeology will find this to be an invaluable resource.
Keywords: Social sciences; Anthropology; Archaeology; Social Sciences; Archaeology; Anthropology